Corrosion Experimental Research on Local Damage of Epoxy-Coated Steel Bars in Concrete Under Marine Environment - Cao, Hongfei; Lyu, Zhongda; Dong, Wei; Zhao, Zhuo; Gan, Weizhong; Wang, Yonggang (Frontiers in Materials, 2022)
Epoxy coating has been proven to protect steel bars from corrosion. However, the damage of epoxy steel bar is inevitable, when the damage of epoxy coating occurs, the steel bar may be more serious corrosion. In order to study the corrosion resistance of epoxy coating damaged steel bar, two groups of coating damaged bar and one group of coating intact rebar were designed and six specimens were made. The influence of electrolyte concentration on corrosion rate of steel bar was studied by setting different concentration. After 30 days of accelerated corrosion, electrochemical data were recorded by electrochemical workstation. The experimental result shows that the steel bars with coating damage have obvious polarization curve characteristics of corrosion, and the corrosion resistance decreases obviously. According to the corrosion current and potential, the larger the damaged area of the coating, the faster the corrosion rate. According to the polarization curve data, the polarization resistance is modified, and the result is closer to the real polarization resistance value. The calculated corrosion rate shows that the corrosion rate of reinforcement is affected by both electrolyte concentration and coating damage area, and electrolyte concentration has a greater influence on the corrosion rate.